2010
DOI: 10.1017/s0029665110002570
|View full text |Cite
|
Sign up to set email alerts
|

In silico evidence supports a role for DNA methylation in Sirt1-mediated effects of dietary restriction

Abstract: Dietary restriction (DR) remains one of the most robust dietary interventions proved effective to increase lifespan across evolutionarily distinct species, from yeast to rodents (1) . The NAD-dependent (class III) histone deacetylase Sirt1 in mammals, and its orthologue in other species, may be pivotal in mediating the effect of DR to increase lifespan. Ageing is associated with changes in genome methylation (e.g.(2) ), which may be causative in the ageing process. Such observations, in view of the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(7 reference statements)
2
0
0
Order By: Relevance
“…We are addressing this hypothesis through a number of approaches. In silico analysis of overlaps between groups of mouse genes that bind Sirt1, show a change in expression in response to DR or have been identified as undergoing a change in methylation status in older compared with younger animals revealed that all overlaps were greater than expected by chance, lending overall support to our hypothesis ( 85 ) . We have developed a cell line model of SIRT1 overexpression and knockdown, which we are using to confirm Sirt1-dependent changes in methylation and expression of genes highlighted through this in silico analysis and also to analyse the transcriptomic response to Sirt1 manipulation, to investigate if genes/pathways affected by DR and/or ageing-dependent changes in methylation status and/or with links to processes relevant to ageing are affected.…”
Section: Do Beneficial Effects Of Dietary Restriction Include Responssupporting
confidence: 75%
See 1 more Smart Citation
“…We are addressing this hypothesis through a number of approaches. In silico analysis of overlaps between groups of mouse genes that bind Sirt1, show a change in expression in response to DR or have been identified as undergoing a change in methylation status in older compared with younger animals revealed that all overlaps were greater than expected by chance, lending overall support to our hypothesis ( 85 ) . We have developed a cell line model of SIRT1 overexpression and knockdown, which we are using to confirm Sirt1-dependent changes in methylation and expression of genes highlighted through this in silico analysis and also to analyse the transcriptomic response to Sirt1 manipulation, to investigate if genes/pathways affected by DR and/or ageing-dependent changes in methylation status and/or with links to processes relevant to ageing are affected.…”
Section: Do Beneficial Effects Of Dietary Restriction Include Responssupporting
confidence: 75%
“…In silico analysis of overlaps between groups of mouse genes that bind Sirt1, show a change in expression in response to DR or have been identified as undergoing a change in methylation status in older compared with younger animals revealed that all overlaps were greater than expected by chance, lending overall support to our hypothesis (85) . In silico analysis of overlaps between groups of mouse genes that bind Sirt1, show a change in expression in response to DR or have been identified as undergoing a change in methylation status in older compared with younger animals revealed that all overlaps were greater than expected by chance, lending overall support to our hypothesis (85) .…”
Section: Do Beneficial Effects Of Dietary Restriction Include Responssupporting
confidence: 74%